ANALISA PERBANDINGAN ARSITEKTUR DATA CENTER SWITCH CENTRIC DAN SERVER CENTRIC PADA SISTEM E-VOTING - Huwae, Raphael Bianco; Jatmika, Andy Hidayat; Alamsyah, Noor (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2023)
The development of e-voting was first introduced in the United States in 1974. Various countries around the world have also implemented e-voting using Electronic Voting Machines (EVMs), the internet, mobile phones, fax, and other technologies to facilitate the electoral process. Meanwhile, in Indonesia, the voting system is currently conducted solely through legislative and voting systems such as paper ballots or checkmarks. Therefore, in building an e-voting system, a Data Center is needed to store, process, disseminate data, accelerate the electoral process, and prevent the fraud that has been observed in traditional elections. This often leads to the idea of an e-voting system that is expected to effectively and efficiently accommodate all electoral principles while ensuring that democratic principles are upheld.